The impact of vaccine hesitation on the intentions to get COVID-19 vaccines: The use of the health belief model and the theory of planned behavior model - Li, Zeming; Ji, Ying; Sun, Xinying (Frontiers in Public Health, 2022)
Object: During the later period of the COVID-19 pandemic, the public has been at risk of the evolving COVID-19 variant strain and hesitate to be vaccinated against COVID-19 to a certain extent. In this context, the health belief model and the theory of planned behavior model were used to compare and summarize the relationship between vaccine hesitation/non-hesitation and the intentions of the future COVID-19 vaccine and its influencing factors. Methods: We designed and implemented a cross-sectional, population-based online survey. 1757 respondents entered the final analysis, of which 51.05% (n=897) had vaccine hesitation, and 48.95% had no hesitation. Results: This study found that education background is one of the factors influencing vaccine hesitation. Most people with high education do not hesitate (65.24%), while a more significant proportion of people with low education have vaccine hesitation (66.00%). According to HBM, for the vaccine hesitation group, self-efficacy, family advice, and doctor's advice were the most critical factors affecting the public's future vaccination intentions; for the vaccine non-hesitation group, self-efficacy, doctor's advice, and perceived benefits are the most important influencing factors. According to the TPB, the subjective norm is the most critical factor affecting the future vaccination intention of the vaccine hesitation group, and the attitude towards behavior is the most critical factor affecting the future vaccination intention of the vaccine non-hesitation group. Conclusions: In the context of COVID-19, the public's hesitation on the "current" vaccines will still affect future vaccination intentions. Using HBM and TPB would help health policymakers, and healthcare providers formulate intervention plans.